2008
DOI: 10.1080/17482960802163622
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain-based computerized neuroimaging in ALS and other motor neuron disorders

Abstract: Advanced neuroimaging applications to patients suffering from ALS and other motor neuron disorders (MND) have a high potential in terms of understanding the pathophysiology and visualizing the in vivo pathoanatomy of the diseases. In this context, particularly observer-independent computerized analyses of magnetic resonance imaging (MRI) data are of special interest since they overcome shortcomings of region-of-interest-based techniques. For three-dimensional structural T1-weighted MRI of the whole brain, voxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 74 publications
4
25
0
Order By: Relevance
“…33 Beyond the minority of ALS cases with frank FTD, significant atrophy of either GM or WM is not typical. MRI is potentially more sensitive to such changes, and several studies have demonstrated widespread GM changes including regional overlap with our study 18,27,[34][35][36] (reviewed in reference 37 ). While the involvement of the temporal lobes we noted is in keeping with the known spectrum of cognitive and pathologic overlap with FTD, none of our subjects had overt cognitive impairment, and we do not draw any firm conclusions in the absence of formal neuropsychological assessment.…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 59%
“…33 Beyond the minority of ALS cases with frank FTD, significant atrophy of either GM or WM is not typical. MRI is potentially more sensitive to such changes, and several studies have demonstrated widespread GM changes including regional overlap with our study 18,27,[34][35][36] (reviewed in reference 37 ). While the involvement of the temporal lobes we noted is in keeping with the known spectrum of cognitive and pathologic overlap with FTD, none of our subjects had overt cognitive impairment, and we do not draw any firm conclusions in the absence of formal neuropsychological assessment.…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 59%
“…In a study of 80 ALS patients, Abe et al 21 found that 65% of patients and 51% of controls showed hyperintensity of the posterior limb of the internal capsule on both T2 and proton density sequences. Several recent reviews on the role of MRI as a biomarker for ALS have thus concluded that the finding of CST hyperintensity on T2, FLAIR or PD cannot be considered a reliable indicator because of its poor sensitivity and specificity [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…In proton-density images, foci of frontal abnormalities were observed, indicating involvement of frontal projections. In addition, fluid-attenuated inversion recovery (FLAIR) images were slightly more sensitive in detecting CST signal alterations than T1w or T2w images (see Grosskreutz and colleagues for a review) [Grosskreutz et al 2008]. Also for the diagnosis of primary lateral sclerosis (PLS), MRI signs are described, that is, abnormalities (atrophy) in the precentral gyrus region and CST hyperintensities [Singer et al 2007].…”
Section: Diagnostic Role Of Neuroimaging In Motor Neuron Diseasesmentioning
confidence: 99%